Vortex-induced Vibration and Control of Split Three-Box Girder Bridges. Issue 1 (2nd January 2023) - Yang, Fengfan; Zheng, Shixiong; Yan, Zhengxi
Abstract: The vortex-induced vibration (VIV) performance and aerodynamic mechanism of VIV control of a split three-box girder bridge were investigated numerically by Computational Fluid Dynamics (CFD). Large-scale section model wind tunnel tests show that the integrated countermeasure combined by 30% ventilation ratio grids and new scheme for maintenance tracks can effectively restrain vertical and torsional VIVs. The reliability of numerical method is verified by comparing static three-component coefficients and Strouhal numbers obtained from CFD and wind tunnel tests. The flow structure and changes of aerodynamic forces were analyzed via delayed detached-eddy simulation (DDES). For the original section, large-scale vortices form with shedding behind the safety barrier of the upstream box and behind the maintenance tracks, as well above the downstream highway box, introducing periodic pulsating lifts and moments that result in severe VIVs. The grids can effectively reduce the size of vortices in the gaps, prevent the flow from fluctuating and reduce the pressure difference between upper and lower surfaces. The torsional VIVs at non-negative attack angles are not controlled because the grids cannot interfere with the vortices behind the maintenance tracks. The new scheme for maintenance tracks, which has grid-like effects, can eliminate the torsional VIVs at non-negative attack angles by preventing the vortices behind maintenance tracks from impacting downstream boxes. The aerodynamic force components are analyzed to find that box 1 mainly contributes the mean values and box 3 mainly contributes the fluctuating values. The integrated countermeasure can reduce the mean and RMS values of aerodynamic forces to varying degrees. The streamlines and RMS pressure contours indicate that the integrated countermeasure effectively reduced the wake height and vortices motion range, which is conducive to VIV control. This work lays a solid foundation for an in-depth understanding of the aerodynamic characteristics and optimization mechanism of split three-box girder bridges.